The antinomian framework of Western and non-Western democracies—from theory to application - Hidalgo, Oliver Fernando (Frontiers in Political Science, 2025)
This article argues in favour of broadening the classical paradigm of democracy that historically emerged in the West. Without disregarding the undiminished significance of the idea of liberal democracy and its deep commitment to universal human rights, the necessity of a new accentuation of the concept of democracy is accepted in view of the observable democratic processes in non-Western societies. This should help to avoid both the blind spots of Eurocentrism and the misperception of countries as democracies that are merely masking their authoritarian or despotic character. The result is a theory of popular sovereignty that seeks to grasp and combine Western and non-Western conceptions of democracy in a balanced way and is based on a genealogical and comparative perspective of the history of political ideas in the global North and South. In a second step, the theory is then tested using a few selected examples (Confucian democracy, Islamic democracy, African democracy).